The Traffic in Hierarchy: Masculinity and Its Others in Buddhist Burma, by Ward Keeler. (10th February 2021) - Coleman, Tracy
Abstract : The Traffic in Hierarchy: Masculinity and Its Others in Buddhist Burma, by Ward Keeler. Honolulu: University of Hawai'I Press, 2017. 350 pp., $72 (hb), $30 (pb). ISBN: 978-0-82-486594-8 (hb), 978-0-82-488312-6 (pb).